Students’ Mathematical Errors: A Responsibility of the Teachers (Pragyaratna प्रज्ञारत्न, 2024)
Among the roles and responsibilities of numerous factors for the formation of students’ errors, the specific objective of this research was to explore mathematics teachers’ insight with reference to their own teaching role that how far it was responsible to evolve and develop students’ mathematical errors. So, the study collected, analyzed and theorized the views and experiences of mathematics teachers regarding students’ mathematical errors which could be formed because of teachers’ different teaching styles and processes. There were four main areas of investigation to explore that how teaching/learning (T/L) process lead by the teachers is accountable for seeding mathematical errors in students’ learning progression. The study has basically followed a qualitative research design though it has processed some simple factual data. Thus, the perceptual information was supplemented and strengthened by the factual data gathered from the survey task. As a data collection procedure, it adapted interview, focus group discussion (FGD) and survey. For this, the required research tools developed were interview and FGD guidelines along with a set of surveying questionnaire. The qualitative information was coded as per the main themes of investigation of four areas and then they were critically judged, analyzed, and interpreted. At the end, the findings of the study were strengthened by a triangulation process with reference to relevant theories and previous research studies of the same field.